Assessing the association between hoof thermography and hoof Doppler ultrasonography for the diagnosis of lameness in horses - Douthit, Teresa L.; Bormann, Jennifer M.; Bello, Nora M. (My University, 2014)
The objectives of this study were to 1) assess the correlation between hoof surface temperature and ultrasonographic measurements of digital blood vessels in horses, and 2) evaluate their potential as predictors for clinical lameness. Twelve 3-year-old American Quarter Horses, 6 geldings and 6 mares, with average initial body weight of 459 ± 31 kg were utilized. On days 0, 30, 60, and 90 of the study, horses were weighed and subjected to clinical lameness exams. Doppler ultrasonography was used to measure diameter of the medial palmar artery in the distal left forelimb and velocity of blood flow through that artery starting at 60 min after morning feeding and repeated at 30-min intervals. Temperature measurements on the hoof were collected at 15-min intervals beginning 75 min after feeding using a digital thermographic camera. A series of bivariate linear mixed models were fitted to estimate the correlation between Doppler and temperature measurements. The within-horse and between-horse correlations between hoof surface temperature and velocity of blood flow in the distal limb through the medial palmar artery was estimated at 0.40 (P > 0.50) and 0.99 (P < 0.001), respectively. These results indicate that, at the horse level, the correlation between hoof temperature and velocity of blood flow in the distal limb was very high, but within horse, this correlation was not significantly different from zero. Velocity of blood flow at 60 min after feeding improved model fit to the lameness data, so was included as a model predictor for lameness.
Keywords: Doppler ultrasonography; Horse; Lameness; Thermography